Structural-functional changes in the proventriculus of poultry infected with transmissive viral proventriculitis G. I. : ст. - Kotsyumbas, G. I.; Zhyla, M. I.; Tyshkivska, A. M.; Kalinina, O. S.; Khmil, E. P.; Shkil, M. I.; Mysiv, O. V.; Tyshkivsky, M. Y. (My University, 2023)
Transmissive viral proventriculitis (TVP) is a new avian disease, the etiology and pathogenesis and diagnostics of which remain unidentified, being therefore a subject of an active ongoing discussion among researchers and veterinary doctors. Cases of the disease have been reported and registered in many countries of the world. On poultry farms of Ukraine, this disease started to be diagnosed in 2019, according to the characteristic pathognomic changes. The article presents the results of pathoanatomical, histological and electronic-microscopical studies of the glandular part of the stomach of 62 ill broiler chickens aged 24-28 days and 7 clinical healthy broiler chickens of the same age. The samples of the proventriculus from the infected and clinically healthy chickens were fixated in 10% aqueous solution of neutral formalin and in 1.5% solution of glutaraldehyde in 0.2 molar cacodylate buffer (рН 7.2). Pathoanatomic necropsy of the infected broiler chickens revealed overall anemia, decrease in the volume of the spleen, thymus and fecal sac. In the glandular part of the stomach, the wall was slightly thickened, non-homogenously stained on the section, the mucous membrane being swollen, covered by dense whitish mucous. According to the histological study, the proventriculus of the broiler chickens had lymphocytic necrotizing proventriculitis. In the tubular-alveolar structures of the mucous membrane, there prevailed alteration of the secretory epithelium, with its transformation into ductal epithelium, combined with lymphocytic infiltration of the interstitium. Intensive necrosis of most glandular (oxynticopeptic) cells was accompanied by their exfoliation from the basal membrane of the secretory parts, with desquamated cells accumulating in enlarged lumens of alveoli and excretory ducts. Further, necrotized oxynticopeptic cells in the tubular-alveolar glands were actively replaced by cylindrical ductal cells, and also their hyperplasia and hypertrophy occurred. Diffusive and multifocal interalveolar round-cell infiltrates were mostly presented by lymphocytes, among which there occurred plasmocytes, macrophages, and heterophils. Ultrastructural studies of secretory cells revealed presence of pathogen virions in nucleus and cytoplasm. Based on the morphological changes in the birds’ proventriculus, we diagnosed transmissive viral proventriculitis, which had not been recorded in Ukraine before.
Regulatory Mechanisms in Biosystems
Keywords: передшлунок птиці; avian TVP; proventriculus chickens; провентрикуліт